Trade strategy, structural adjustment and the balance of payments : a survey. - McIntyre, Arnold (1990)
Reviews the policy content of present IMF/World Bank approaches to 'outward oriented' development strategies designed to produce export-led growth. Points to the need for strategic planning in the region which identifies priority exports and the necessary and sufficient requirements that would need to be put in place over some specific period for the development of these exports.